2016
DOI: 10.2319/111615-777.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of staining and color changes of a resin infiltration system

Abstract: Objective: To analyze the staining and color changes of a resin infiltrant system used for management of white spot lesions (WSLs). Materials and Methods: WSLs were artificially created on left buccal halves of 48 extracted human teeth. These sites were then treated with resin infiltration (RI) while the right halves of the teeth remained as nonresin (NRI) areas. Six groups were formed (n ¼ 8 teeth/group) and were exposed to the following: red wine, coffee, orange juice, combined staining agents, accelerated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 25 publications
4
28
1
Order By: Relevance
“…Regarding surface roughness, our results agreed with previous studies which concluded that resin infiltration of enamel lesions can provide and maintain smoother surface. However, these results contrast those of other researches which reported that surface roughness and color stability of resin‐infiltrated enamel lesions were less than ideal and could further recede with aging in the oral environment. This disagreement may be a result of mismatching in the experimental conditions and evaluation methods.…”
Section: Discussioncontrasting
confidence: 94%
“…Regarding surface roughness, our results agreed with previous studies which concluded that resin infiltration of enamel lesions can provide and maintain smoother surface. However, these results contrast those of other researches which reported that surface roughness and color stability of resin‐infiltrated enamel lesions were less than ideal and could further recede with aging in the oral environment. This disagreement may be a result of mismatching in the experimental conditions and evaluation methods.…”
Section: Discussioncontrasting
confidence: 94%
“…Another study tested Icon color change when placed on artificial white spot lesions made in extracted teeth. 30 That study found that, although significant staining occurred in lesions restored with the infiltrative resin, use of a prophylaxis treatment greatly diminished the effect. Clinical implications of the current study are great.…”
Section: Discussionmentioning
confidence: 95%
“…The clinical recommendation from that study was that, although Icon tended to stain over time, avoidance of staining foods and beverages can enhance the esthetic outcome of these restorations. Another study tested Icon color change when placed on artificial white spot lesions made in extracted teeth . That study found that, although significant staining occurred in lesions restored with the infiltrative resin, use of a prophylaxis treatment greatly diminished the effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations